2020
DOI: 10.2147/ijn.s250367
|View full text |Cite
|
Sign up to set email alerts
|

<p>Zinc Oxide Nanoparticles Induce Ferroptotic Neuronal Cell Death in vitro and in vivo</p>

Abstract: Purpose Zinc oxide nanoparticles (ZnONPs) are one of the most important nanomaterials that are widely used in the food, cosmetic and medical industries. Humans are often exposed to ZnONPs via inhalation, and they may reach the brain where neurotoxic effects could occur via systemic distribution. However, the mechanisms underlying how ZnONPs produce neurotoxic effects in the brain remain unclear. In this study, we aimed to investigate the novel mechanism involved in ZnONPs-induced neurotoxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…The failure to do so indicates an error in the reference memory while the working memory is assessed when the mouse made an entry to each arm a single time. Re‐entry into the arms with no food reward would be considered as working memory error [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The failure to do so indicates an error in the reference memory while the working memory is assessed when the mouse made an entry to each arm a single time. Re‐entry into the arms with no food reward would be considered as working memory error [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study on ICH suggested that the JNK pathway could be initiated, with upregulation of pJNK (Hibi et al, 1993;Pei et al, 2016). Other studies indicated that JNK is involved in ferroptotic cell death in mouse cortex and PC-12 cells (Qin et al, 2020). TNFAIP3, an important anti-inflammatory factor, can repress the expression of inflammatory NF-κB signaling and promote cell survival (Catrysse et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc oxide nanoparticles (ZnONPs) interfere with iron homeostasis and ROS production, ultimately leading to ferroptosis 30 . The ferroptosis induced by ZnONPs is JNK and p53 dependent, as JNK, inhibitor and p53 siRNA abrogate this effect 30,31 . Besides, other nanomaterials such as Al 2 O 3 , Fe 3 O 4 , and TiO 2 also cause intracellular Fe 2+ elevation in HUVECs 30 .…”
Section: Discussionmentioning
confidence: 99%